Long-term monitoring of SO2 quiescent degassing from Nyiragongo’s lava lake - Arellano, Santiago; Bobrowski, Nicole (Journal of African earth sciences, 2017)
The activity of open-vent volcanoes with an active lava-lake, such as Nyiragongo, is characterized by persistent degassing, thus continuous monitoring of the rate, volume and fate of their gas emissions is of great importance to understand their geophysical state and their potential impact. We report results of SO2 emission measurements from Nyiragongo conducted between 2004 and 2012 with a network of ground-based scanning-DOAS (Differential Optical Absorption Spectroscopy) remote sensors. The mean SO2 emission rate is found to be 13 ± 9 kg s−1, similar to that observed in 1959. Daily emission rate has a distribution close to log-normal and presents large inter-day variability, reflecting the dynamics of percolation of magma batches of heterogeneous size distribution and changes in the effective permeability of the lava lake. The degassed S content is found to be between 1000 and 2000 ppm from these measurements and the reported magma flow rates sustaining the lava lake. The inter-annual trend and plume height statistics indicate stability of a quiescently degassing lava lake during the period of study.
Available online 11 July 2016
Gesehen am 12.07.2018